Analysis of Factors Influencing Taxpayer Compliance in Carrying Out Tax Obligations (Literature Review) - Hendra Apriwarto , Muhammad (PT. Maju Malaqbi Makkarana, 2024)
The study concludes that taxpayer compliance is driven by various economic, social-psychological, and demographic factors. Economic factors, such as reasonable tax rates and the enforcement of effective penalties, play a significant role in improving compliance. Additionally, social-psychological aspects, including increased tax awareness, trust in government, and social norms, are critical in influencing taxpayer behavior. Demographic characteristics, such as age, education, and income levels, also affect compliance likelihood. To foster higher tax compliance, governments must adopt a comprehensive strategy that combines economic incentives, social influence, and educational initiatives. Addressing these diverse factors can lead to a more efficient tax system and encourage voluntary compliance among taxpayers.